PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT LOYALITAS PELANGGAN PADA LAUNDRY SEKHA CLEAN CIANJUR - Artyanto, Cahya Iman; Tiris Sudrartono, Tiris Sudrartono (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The purpose of this study was to analyze the effect of service quality on the level of customer loyalty at Laundry Sekha Clean Cianjur. This study uses descriptive quantitative methods with the data collection technique used, namely the distribution of questionnaires distributed via google form. Respondents in this study totaled 55 people who were Sekha Clean customers who used laundry services at least 2 times during the last 6 months. This research is motivated by the decline in the number of visitors at the Sekha Clean Cianjur Laundry in the period January-August 2023. The decrease in the number of visitors to Sekha Clean shows a decrease in the level of satisfaction and loyalty of customers, one of which is caused by the quality of service provided less than optimal. The results showed that service quality had a 74.5% effect on customer loyalty. Based on the T test results, the t_count value is 9.446> t_table 1.673 with a significance level of 0.01 <0.05, it can be said that H0 is rejected while H1 is accepted, which means that Variable X (Service Quality) has an influence on Variable Y (Customer Loyalty).